Tailoring the ORR selectivity for H2O2 electrogeneration by modification of Printex L6 carbon with 1,4-naphthoquinone: a theoretical, experimental and environmental application study - Kronka, Matheus S. [UNESP]; Silva, Fernando L.; Martins, Alysson S. [UNESP]; Almeida, Michell O.; Honorio, Kathia M.; Lanza, Marcos R. V. [UNESP] (Royal Soc Chemistry, 2020)
The modification of carbon-based materials with electroactive organic compounds can improve the oxygen reduction reaction (ORR) efficiency toward H2O2 electrogeneration. The present work sought to evaluate the electrochemical properties of a Printex L6 carbon matrix modified with 1,4-naphthoquinone (NQE) and its application toward the removal of paracetamol in different advanced oxidation processes. The 1.0% NQE-modified material showed 93% selectivity for H2O2 electrogeneration compared to 85% for the unmodified carbon matrix. Density functional theory calculations helped confirm the NQE action as an H+ donor by improving the Delta G of the reaction from -277.11 kJ mol(-1) for PL6C to -986.1 kJ mol(-1) for the NQE-modified material. Applied at 75 mA cm(-2), the modified gas diffusion electrode presented a 30% increase in H2O2 electrogeneration compared to the unmodified electrode. Paracetamol removal followed pseudo-first-order reaction kinetics in the following order: anodic oxidation with H2O2 electrogeneration (AO-H2O2) < AO-H2O2/UVC < electro-Fenton (EF) < photoelectro-Fenton (PEF). The action of the NQE modifier helped enhance the ORR activity and selectivity for H2O2 electrogeneration, thus making the material suitable for environmental application in wastewater treatment.